2019
DOI: 10.1016/j.ctrv.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

PARP inhibitors in ovarian cancer

Abstract: Poly-ADP-ribose polymerase inhibitors (PARPis) are the most active and interesting therapies approved for the treatment of epithelial ovarian cancer. They have changed the clinical management of a disease characterized, in almost half of cases, by extreme genetic complexity and alteration of DNA damage repair pathways, particularly homologous recombination (HR) deficiency. In this review, we provide an updated overview of the available results of recent clinical trials on the three Food and Drug Administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 68 publications
1
135
0
1
Order By: Relevance
“…Last, in 2018, olaparib and talazoparib were approved for human epidermal growth factor receptor type 2 (HER2)-negative locally advanced or metastatic breast cancer with germline BRCA1/2 mutations. Multiple clinical trials carried out since 2009 have demonstrated PARP inhibitor efficacy in BRCA mutated ovarian and breast cancer, but also prostate, pancreatic cancer, and small cell lung carcinoma (SCLC), irrespective of the BRCA status (Weaver and Yang 2013;Sonnenblick et al 2015;Mirza et al 2018;Franzese et al 2019;Keung et al 2019;Mateo et al 2019;Pant et al 2019;Pilie et al 2019a). Inhibitors of poly(ADP-ribose) glycohydrolase (PARG) joined the stage once structures of the PARG catalytic site became available (Slade et al 2011;Dunstan et al 2012;Kim et al 2012; Barkauskaite et al 2013).…”
mentioning
confidence: 99%
“…Last, in 2018, olaparib and talazoparib were approved for human epidermal growth factor receptor type 2 (HER2)-negative locally advanced or metastatic breast cancer with germline BRCA1/2 mutations. Multiple clinical trials carried out since 2009 have demonstrated PARP inhibitor efficacy in BRCA mutated ovarian and breast cancer, but also prostate, pancreatic cancer, and small cell lung carcinoma (SCLC), irrespective of the BRCA status (Weaver and Yang 2013;Sonnenblick et al 2015;Mirza et al 2018;Franzese et al 2019;Keung et al 2019;Mateo et al 2019;Pant et al 2019;Pilie et al 2019a). Inhibitors of poly(ADP-ribose) glycohydrolase (PARG) joined the stage once structures of the PARG catalytic site became available (Slade et al 2011;Dunstan et al 2012;Kim et al 2012; Barkauskaite et al 2013).…”
mentioning
confidence: 99%
“…PARPs catalyze a reaction in which the ADP-ribose moiety of NAD + is transferred to a receptor amino acid, building poly(ADP-ribose) (PAR) polymers (MĂ©gnin-Chanet et al, 2010). PARP-1, the founding member of the PARP superfamily, has been demonstrated to regulate the growth of various tumor cells, such as breast cancer, ovarian cancer, and NPC (Chen, Zhao, et al, 2015;Franzese et al, 2019;Nur Husna, Tan, Mohamud, Dyhl-Polk, & Wong, 2018). PARP-2 possesses a catalytic domain structurally similar to PARP-1, whereas it is less active than PARP-1 (Ali et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[25] Drugs that have shown efficacy in BRAC1/2 carriersw ith de-ficientH Rr epair ovarian cancers include poly(ADP-ribose) polymerase (PARP) inhibitors such as olaparib, rucaparib,a nd niraparib. [26] Cancer cells use PARP proteins in av ariety of DNA damage repair mechanisms and the inhibition of PARP can trigger death of cancerc ells via synthetic lethality when another mechanism for repairing DNA is defective. PARP inhibitors have traditionally been used in platinum sensitive cancers, but in ar ecent Phase II clinical trial, single agent olaparib treatment showed favorable responses in women with OCpt, including those with BRCA wild-type disease (ClinicalTrials.gov information:N CT02822157).…”
Section: Dysfunctional Dna Repairmentioning
confidence: 99%